Long Term Non-invasive Ventilation in Children With Central Hypoventilation - Paglietti, Maria Giovanna; Esposito, Irene; Goia, Manuela; Rizza, Elvira; Cutrera, Renato; Bignamini, Elisabetta (Frontiers in Pediatrics, 2020)
Abstract: Central hypoventilation (CH) is a quite rare disorder caused by some congenital or acquired conditions. It is featured by increased arterial concentration of serum carbon dioxide related to an impairment of respiratory drive. Patients affected by CH need to be treated by mechanical ventilation in order to achieve appropriate ventilation and oxygenation both in sleep and wakefulness. In fact, in severe form of Congenital Central Hypoventilation Syndrome (CCHS) hypercarbia can be present even during the day. Positive pressure ventilation via tracheostomy is the first therapeutic option in this clinical condition, especially in congenital forms. Non-Invasive ventilation is a an option that must be reserved for more stable clinical situations and that requires careful monitoring over time.